Role of Atenolol and Carvedilol in Prevention of Adrenaline Induced Myocardial Infarction: A Comparative Study on Experimental Animal (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: In some trials in United States of America (USA) and Bangladesh, vasodilating non selective β blockers (e.g. carvedilol, propranolol etc.) have been shown to be better tolerated than nonvasodilating β1 selective blocker (e.g. atenolol, metoprolol etc.) to prevent cardiovascular diseases (Coronary Heart Disease, Ischemic Heart Disease and other cardiovascular conditions)Objective: To compare the role of atenolol and carvedilol in the prevention of adrenaline induced myocardial infarction (MI) in experimental animal (rats).Materials and Methods: This experimental study was carried out in the Department of Pharmacology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka for a period of one year (from July 2014 to June 2015). Seventy two (72) healthy rats of Long Evan Norwegian strains, 3-4 months of ages of both sexes, weight between 180-220g were used. These rats were randomly selected and ethical issues were addressed. In this study cardio-protective effect was assessed by measuring the serum enzymes (CK-MB and AST) levels and antiperoxidative action was estimated by the hepatic and cardiac reduced glutathione (GSH) contents in experimentally (adrenaline) induced myocardial infarction.Results: Adrenaline (2mg/kg) induced myocardial damage in rat model was evaluated biochemically by significant (P